The Quick Exposure Check (QEC) Model Proposal Based on Fuzzy Logic for Work-Related Musculoskeletal Risk Assessment - Kose, Yildiz; Karabayir, Ayse Nur; Cevikcan, Emre (Springer International Publishing, 2019)
Work-related musculoskeletal disorders (WMSDs) are one of the most common health problems in the community. Self-reports, observational methods, and direct measurements techniques are used to detect exposure and changes in exposure to risk factors for WMSD, especially in industrialized countries. By using these techniques to perform musculoskeletal risk analyzes, the health problems and disability of the employees will be prevented. The Quick Exposure Check (QEC) is a method used to quantify the risk of musculoskeletal risks, combining observations and participant notifications. The QEC is the basis for ergonomic regulations at work. It is also used to evaluate the effectiveness of any intervention. Fuzzy Logic has not yet been proposed for risk assessment in the QEC. In this context, this paper contributes to the relevant literature by means of developing a risk analysis. In this study the QEC technique based on Fuzzy Logic was used in risk assessments. In the case of the absence of crisp data in the exposure levels evaluation of observers and workers in the QEC technique, the classical evaluation ratings are insufficient. Therefore, fuzzy logic has been used for more sensitive results in linguistic evaluations.